Chemoselective Epoxidation of Allyloxybenzene by Hydrogen Peroxide Over MFI‐Type Titanosilicate. Issue 15 (30th March 2020) - Kon, Yoshihiro; Nakashima, Takuya; Hong, Dachao; Ji, Xinyi; Osuga, Ryota; Ito, Satoru; Fujitani, Tadahiro; Sato, Kazuhiko; Yokoi, Toshiyuki
Abstract : The chemoselective synthesis of 2‐(phenoxymethyl)oxirane from allyloxybenzene is achieved with over 90 % yield in a sustainable reaction system using titanium‐substituted silicalite‐1 (TS‐1) as a catalyst, hydrogen peroxide (H2 O2 ) as an oxidant, and a mixture of MeOH/MeCN as a solvent at 40 °C. No acid‐catalyzed side reactions prompted by the Lewis acidity of the Ti active site in TS‐1 are observed. The TS‐1 catalyst can also promote the formation of oxiranes from various p ‐substituted allyloxybenzenes in good yields. The reaction mechanism is investigated through the reaction with other allyloxy compounds. The results, which are supported by DFT calculations, indicate that an active species of Ti peroxides formed from the reaction of TS‐1 with H2 O2 selectively oxidizes the allyloxybenzene to 2‐(phenoxymethyl)oxirane. Abstract : A H2 O2 chemoselective epoxidation of allyloxybenzene was developed using titanium‐substituted silicalite‐1 (TS‐1) as catalyst. The gram‐scale synthesis of 2‐(phenoxymethyl)oxirane was performed using 5.30 g of allyloxybenzene to produce 5.21 g of 2‐(phenoxymethyl)oxirane in 93 % isolated yield. MeOH/MeCN as mixed solvent facilitated the desired epoxidation even at 40 °C. The developed TS‐1 catalyst is reusable, productive, and has a broad substrate scope.